PEMBUATAN FILM KOMPOSIT KITOSAN –TAPIOKA : PENGARUH KOMPOSISI TERHADAP KARAKTERISTIK FILM - Rokhati, Nur Rokhati; Pramudono, Bambang; Widiasa, I. Nyoman (METANA, 2013)
Abstract Cassava starch can readily be cast into films. However, the cassava starch film is brittle and weak leading to inadequate mechanical properties. Therefore it is necessary blending with other biopolymers that can overcome these drawbacks. In this study, composite film prepared by blending of cassava starch and chitosan solutions with ratio 2:8, 3:7, 4:8, and 5:5. The results show that the mechanical strength of the film increase with increasing the chitosan content. The significant decline in both permeability and degree of swelling with increasing the content of chitosan in the composite film. The hydrophobic acetyl groups of chitosan caused a notable reduction of wettability as well as water permeability. The degree of swelling experiments showed that the films have the highest degree of swelling in water followed by technical ethanol (±95%) and pure analysis ethanol (>99.9%). SEM photographs of the surface of film with the ratio 5:5 have more homogeneous than the ratio 2:8. The amino group peak in IR spectrum of chitosan molecule shifted from 1581 to 1587 cm−1 with the incorporation of starch. These results suggested that these two film-forming components were compatible and an interaction existed between them. Keywords: Chitosan–starch films; composition, characterization